Model Pencegahan Tindak Pidana Terorisme Berbasis Adat Dalihan Na Tolu di Tapanuli Selatan - Harahap, Anwar Sadat; Siregar, Taufik (Pandecta Research Law Journal, 2020)
Beberapa tahun terakhir telah sering terdengar melalui media elektronik tentang tindakan terorisme di Indonesia. Tindak terorisme ini muncul, karena selain kurang tegas, adil dan bermanfaatnya materi pengaturan hukum tentang pencegahan tindak terorisme, juga disebabkan oleh kurang diberdayakannya potensi masyarakat adat dalam mencegah tindak terorisme. Hasil penelitian menunjukkan bahwa: 1) Pencegahan tindak pidana terorisme berdasarkan adat Dalihan na Tolu di Tapanuli Selatan dilakukan dengan aturan yang tercantum dalam: Filosofi adat adat Dalihan na Tolu, Sipaingot, Tutur dan Uhum dohot Patik 2) Jenis sanksi yang dikenakan kepada teroris: Sappal Dila, Dibondarkon, Dipaorot sian Marga, Dipaulak Salipi Natartar, dan Uhum Hatoban.Ã‚Â Various criminal acts of terrorism continue to occur in Indonesia; even the numbers increase from year to year. These various acts of terrorism have arisen because, in addition to being less assertive, the legal provisions concerning the prevention of terrorist acts. Besides, the lack of involvement of indigenous peoples in preventing acts of terrorism as regulated in Article 43B paragraph (4) of Law Number 5 the Year 2018. This study aims to determine the role of Dalihan na Tolu adat in the prevention of criminal acts of terrorism. The research method used is empirical legal research methods. Prevention of criminal acts of terrorism carried out through the rules stated in philosophy, Sipaingot, Tutur, and Uhum dohot Poda. Then the traditional leaders' strategy in preventing the crime of terrorism is done by Providing examples of exemplary, Providing duties in maintaining security and order, Involving the community in every customary activity, and presenting children in customary activities. Furthermore, the types of sanctions imposed on terrorism offenders are: Dibondarkon sanctions (not involved in traditional activities), Sappal Dila sanctions (inviting people to eat in the same village), Dipaorot sian Huta sanctions (issued from villages), Dipaorot sian Marga sanctions (issued from the Marga), sanctions Diapaulak Salipi Natartar (returned to the communal land).